Reference Values of Fetal Peak Systolic Velocity in the Middle Cerebral Artery at 19–40 Weeks of Gestation in Nepalese Population - Shrestha, U; Shrestha, I; Ghimire, RK; Paudel, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The purpose of this study was to construct new reference range for fetal middle cerebral artery peak systolic velocity (MCA-PSV) in uncomplicated pregnancy at 19-40 weeks of gestation. Methods: This was a prospective cross-sectional study involving 400 singleton pregnancies between 19 and 40 weeks of gestation without any known risk factors of adverse pregnancy outcome who were referred for routine obstetric examination. The protocol included the doppler examination of fetal middle cerebral artery (MCA) within 2 mm after its origin from the internal carotid artery and data were used to construct the normograms and percentile fitted curves of each doppler parameter for different gestational age. Results: Among 400 singleton uncomplicated pregnancies between 19 and 40 weeks of gestation maximum number of pregnancies (10%) was at 19 weeks of gestation and minimum (2.5%) was at 31 weeks. The fetal peak systolic blood flow in the MCA showed significant correlation with period of gestation. Mean MCA-PSV was 22.35 ± 3.05 at 19 weeks of gestation which increased to 67.73 ± 9.92 at 40 weeks. The MCA-PSV showed continuous increment with increasing gestational age. Conclusions: Continuous increment in the peak systolic volume with advancing gestational age was obtained which was consistent with the previous studies done by various authors. The percentile fitted values and normograms will be valuable for the serial measurement of the peak systolic volume of the middle cerebral artery for complicated pregnancies. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 42-45 DOI: http://dx.doi.org/10.3126/njog.v8i2.9769